Light‐Responsive Colloidal Crystals Engineered with DNA. Issue 8 (15th January 2020) - Zhu, Jinghan; Lin, Haixin; Kim, Youngeun; Yang, Muwen; Skakuj, Kacper; Du, Jingshan S.; Lee, Byeongdu; Schatz, George C.; Van Duyne, Richard P.; Mirkin, Chad A.
Abstract: A novel method for synthesizing and photopatterning colloidal crystals via light‐responsive DNA is developed. These crystals are composed of 10–30 nm gold nanoparticles interconnected with azobenzene‐modified DNA strands. The photoisomerization of the azobenzene molecules leads to reversible assembly and disassembly of the base‐centered cubic (bcc) and face‐centered cubic (fcc) crystalline nanoparticle lattices. In addition, UV light is used as a trigger to selectively remove nanoparticles on centimeter‐scale thin films of colloidal crystals, allowing them to be photopatterned into preconceived shapes. The design of the azobenzene‐modified linking DNA is critical and involves complementary strands, with azobenzene moieties deliberately staggered between the bases that define the complementary code. This results in a tunable wavelength‐dependent melting temperature ( T m ) window (4.5–15 °C) and one suitable for affecting the desired transformations. In addition to the isomeric state of the azobenzene groups, the size of the particles can be used to modulate the T m window over which these structures are light‐responsive. Abstract : Light‐responsive colloidal crystals are constructed with azobenzene‐tethered DNA to undergo a reversible structural change between assembled and disassembled states under isothermal conditions. Such dynamic control in bonding between nanoparticles allows light‐responsive colloidal crystals to be combined with a photopatterning technique to enable printing of crystalline DNA–nanoparticle thin films into predesigned shapes.